Corticotropin-Releasing Factor: An Ancient Peptide Family Related to the Secretin Peptide Superfamily - Michalec, Ola M.; Chang, Belinda S. W.; Lovejoy, Nathan R.; Lovejoy, David A. (Frontiers in Endocrinology, 2020)
Corticotropin-releasing factor (CRF) is the hypothalamic releasing peptide that regulates the hypothalamic-pituitary-adrenal/inter-renal (HPA/I) axis in vertebrates. Over the last 25 years, there has been considerable discussion on its paralogous genes, urotensin-I/urocortin-1, and urocortins-2 and-3 and their subsequent role in the vertebrate stress response. Phylogenetically, the CRF family of peptides also belong to the diverse assemblage of Secretin- and Calcitonin-based peptides as evidenced by comparative-based studies of both their ligand and G-protein-coupled receptor (GPCR) structures. Despite this, the common origin of this large assemblage of peptides has not been ascertained. An unusual peptide, teneurin-C-terminal associated peptide (TCAP), reported in 2004, comprises the distal extracellular tip of the teneurin transmembrane proteins. Further studies indicated that this teneurin region binds to the latrophilin family of GPCRs. Initially thought to be a member of the Secretin GPCR family, evidence indicates that the latrophilins are a member of the Adhesion family of GPCRs and are related to the common ancestor of both Adhesion and Secretin GPCR families. In this study, we posit that TCAP may be a distantly related ancestor of the CRF-Calcitonin-Secretin peptide family and evolved near the base of metazoan phylogeny.